You are on page 1of 3

𝐹(𝑥) = (4 + √𝑥)(𝑥 3 − 5

)
𝑑 𝑑
= 𝑑𝑥 (4 + √𝑥)(𝑥 3 − 5) + 𝑑𝑥 (𝑥 3 − 5)(4 + √𝑥)

𝑑 1 𝑑
𝑑𝑥
(4 + √𝑥) = 2 (𝑥 3 − 5) = 3𝑥 2
√𝑥 𝑑𝑥

𝑑 𝑑 𝑑 𝑑
= 𝑑𝑥 (4) + 𝑑𝑥 (√𝑥) = 𝑑𝑥 (𝑥 3 ) − 𝑑𝑥
(5) 𝑑

𝑑 1 𝑑
(4) =0 (√𝑥) = 2√𝑥 (𝑥 3 ) = 3𝑥 2 = 3𝑥 3−1 = 3𝑥 2 𝑑𝑥
𝑑𝑥 𝑑𝑥

1 1 𝑑 𝑑
= 0 + 2√𝑥 = (5) =0 (3𝑥 2 − 0) = 3𝑥 2
2√𝑥 𝑑𝑥 𝑑𝑥

1
=2 (𝑥 3 − 5) + 3𝑥 2 (4 + √𝑥):
√𝑥

1
(𝑥 3 − 5) 3𝑥 2 (4 + √𝑥)
2√𝑥

1.(𝑥 3 −5)
= 2√𝑥
= 3𝑥 2 . 4 + 3𝑥 2 . √𝑥

𝑥 3 −5
= = 12𝑥 2 + 3𝑥 2 √𝑥
2√𝑥

𝑥 3 −5
= 2√𝑥
12𝑥 2 + 3𝑥 2 √𝑥

𝑥 3 −5 12𝑥 2 3𝑥 2 √𝑥
= + +
2√𝑥 1 1

𝑥 3 −5 12𝑥 2 .2√𝑥 3𝑥 2 √𝑥 ∙2√𝑥
= 2√𝑥
+ 2√𝑥 + 2√𝑥

𝑥 3 −5+2 ∙ 12𝑥 2 √𝑥+2∙3𝑥 2 √𝑥√𝑥
= 2√𝑥

2 ∙ 12𝑥 2 √𝑥 2 ∙ 3𝑥 2 √𝑥√𝑥

= 2 ∙ 12𝑥 2 √𝑥 = 2 ∙ 3𝑥 3

= 24𝑥 2 √𝑥 = 6𝑥 3

= 𝑥 3 − 5 + 24𝑥 2 √𝑥 + 6𝑥 3

= 𝑥 3 + 6𝑥 3 + 24𝑥 2 √𝑥 − 5

= 7𝑥 3 + 24𝑥 2 √𝑥 − 5

7𝑥 3 + 24𝑥 2 √𝑥 − 5 = 2√𝑥 𝑑𝑥 ∫ 1 + 𝑠𝑒𝑛(𝑥) 1 2 =∫ ∙ 𝑑𝑢 2𝑢 1 + 𝑢2 1+ 1 + 𝑢2 2 =∫ 𝑑𝑢 𝑢2 + 1 + 2𝑢 1 =2∙∫ 𝑑𝑢 𝑢2 + 1 + 2𝑢 1 =2∙∫ 𝑑𝑢 (𝑢 + 1)2 1 =∫ ∙ 1𝑑𝑣 (𝑣)2 1 =∫ 𝑑𝑣 𝑣2 1 =2∙∫ 𝑑𝑣 𝑣2 = 2 ∙ ∫ 𝑣 −2 𝑑𝑣 𝑣 −2+1 =2∙ −2 + 1 𝑥 (tan (2) + 1)−2+1 =2∙ −2 + 1 2 =− 𝑥 𝑡𝑎𝑛 (2) + 1 .

2 =− 𝑥 +𝑐 𝑡𝑎𝑛 ( ) + 1 2 .